Gait Changes Vary among Horses with Naturally Occurring Osteoarthritis Following Intra-articular Administration of Autologous Platelet-Rich Plasma - Mirza, Mustajab H.; Bommala, Prakash; Richbourg, Heather A.; Rademacher, Nathalie; Kearney, Michael T.; Lopez, Mandi J. (Frontiers in Veterinary Science, 2016)
Mechanisms to reduce lameness associated with osteoarthritis (OA) are vital to equine health and performance. This study was designed to quantify response to autologous, intra-articular platelet-rich plasma (PRP) in horses with OA. Kinetic gait analysis was performed on 12 horses with unilateral forelimb lameness and OA in the same limb before and after intra-articular anesthesia (IAA). Radiographs and kinetic data were obtained before, 6 and 16 weeks after PRP administration to same joint 4 weeks after IAA. Statistical evaluations included filtration effect on platelet concentration, relationship between kinetic variable changes after IAA versus PRP in the affected limb, and associations between response to PRP and response to IAA, platelet concentration and radiographic OA. A positive response to IAA or PRP was defined as ≥5% improvement in peak vertical force, vertical impulse or breaking impulse of the affected limb. Out of 10 horses that responded to IAA, 4 responded to PRP at both time points and 2 responded at one. Of 2 horses that did not respond to IAA, one responded to PRP at both time points. Filtration increased platelet concentration significantly. The relationship between kinetic variable alterations of the affected limb after IAA and PRP was not significant, and response to PRP was not associated with response to IAA, platelet concentration or radiographic OA. Changes in kinetic variables following IAA in joints with naturally occurring OA provide a custom standard to assess intra-articular therapy. Kinetic gait changes after intra-articular PRP are variable in horses with moderate to severe forelimb OA.